Prostor v slovenskih literarnovednih študijah - Hladnik, Miran (Slavistična revija, 2012)
The thematization of space in Slovene literary scholarship took place in the context of narratology, genre analyses of rural and regional prose and the historical novel, thematic and intercultural literary historical research. There is a wealth of data on literary space in the notes to Slovene poets and prose writers' collected works, in particular in the critical edition of Ivan Tavčar's works that Marja Boršnik edited. The notes satisfied curiosity about the actual motivations for literary settings and about the spaces in which writers lived. Authorial creativity was discovered in the disjuncture between the literary and historically attested geographical spaces.
Keywords: critical editon; genesis of literary work; kritike; literarna geografija; literarna kartogrfija; literary cartography; literary geography; Slovene literature; slovenska književnost; Tavčar, Ivan, 1851-1923; tekstologija; textology